The Impact of Organizational Culture Toward Organizational Competitiveness at PT. Mega Royal Utama Medan: Pengaruh Budaya Organisasi Terhadap Daya Saing Organisasi Pada PT. Mega Royal Utama Medan - Bestadrian Prawiro Theng; Ika Puspa Satrianny; Sri Aprianti Tarigan; Susanto; Felix Leonardi (Jurnal Kolaboratif Sains, 2024)
The purpose of this research is to analysis the impact of organizational culture toward organizational competitiveness at PT. Mega Royal Utama Binjai Medan. The data is obtain interview and questionare.There have 32 respondent from the company which only work in the office and supervisor only in the company. Whereby the data analysis using descriptive statistic( mean, median, mode), validity, reability, coeficient of corelation, regresion anlysis and hypothesis test. The result from the data is all valid, realible and normal, so the data can be use for futher analize. There have a significant impact the organizational culture toward organizational competitiveness. Where the Ha accepted and Ho rejected Zcount = 4,776 > Ztable = 1,96. Determination (r2) = 85.6% prove the organizational culture impact 85.6% toward organization competitiveness. The writer intend to give some recomedation which are outbond and happy weekend, monthly meeting and open minded discussion, swtiching work day and, give appreciation and recognition.